Development of an electrochemical immunosensor for the detection of HbA1c in serum - Khor, S.M. (2012)
An electrochemical immuno-biosensor for detecting glycosylated haemoglobin (HbA1c) is reported based on glassy carbon (GC) electrodes with a mixed layer of an oligo(phenylethynylene) molecular wire (MW) and an oligo(ethylene glycol) (OEG). The mixed layer is formed from in situ-generated aryl diazonium cations. To the distal end of the MW, a redox probe 1,1 0 -di(aminomethyl)ferrocene (FDMA) was attached followed by the covalent attachment of an epitope N-glycosylated pentapeptide (GPP), an analogon to HbA1c, to which an anti-HbA1c monocolonal antibody IgG can selectively bind. HbA1c was detected by a competitive inhibition assay based on the competition for binding to anti-HbA1c IgG antibodies between the analyte in solution, HbA1c, and the surface bound epitope GPP. Exposure of the GPP modiﬁed sensing interface to the mixture of anti-HbA1c IgG antibody and HbA1c results in the attenuation of ferrocene electrochemistry due to free antibody binding to the interface. Higher concentrations of analyte led to higher Faradaic currents as less anti-HbA1c IgG is available to bind to the electrode surface. It was observed that there is a good linear relationship between the relative Faradaic current of FDMA and the concentration of HbA1c from 4.5% to 15.1% of total haemoglobin in serum without the need for washing or rinsing steps.